Ferritin Level as Independent Predictor of Covid-19 : a Cross Sectional Study - Nur Komariah; Salbiah Salbiah; Betha Ariesanthy Anggraini Nugroho; Suliati Suliati; Aninda Dinar Widiantari; Farida Murtiani (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2022)
COVID-19 is an infectious disease caused by SARS-CoV-2. In severe cases of COVID-19, it is often accompanied by a syndrome known as cytokine storm or cytokine release syndrome (CRS). Serum ferritin levels, increase as the disease worsens. This study aims to see the relationship between ferritin levels and the degree of COVID-19 and evaluate ferritin levels as a predictor of severity in COVID-19 patients at RSPI Prof Dr Sulianti Saroso. This type of research is quantitative with a cross sectional approach. Data analysis using Kruskal Wallis test. Secondary data from medical records of confirmed COVID-19 patients based on the results of PCR examinations during March 2020 to December 2020 who examined ferrittin levels as many as 554 patients. The results showed that the average ferritin level was 164.78, moderate was 524.13, severe was 1377.52 and critical was 1592.46. The results of the analysis with the Kruskal Wallis test obtained P value = 0.000 < (0.05) so it can be explained that there are differences in ferritin levels of the four degrees of disease. This shows that there is an effect of the relationship between ferritin levels and the degree of disease in COVID-19 patients.